STATE FINANCIAL CONTROL: CONCEPTS AND CLASSIFICATION - Verbytska, V.; Yakushkina, V. (Municipal economy of cities. Series: «Economy science», 2024)
The article emphasises that the conditions of the market economy and the development of Ukrainian society require a new conceptual approach to the creation and functioning of the system of state financial control. Additionally, the significant growth of financial abuses and violations necessitates a fundamental theoretical study and the determination of ways to build a new, better system of state financial control that can solve the problem of inefficient management in the public sector of the economy. The article contains a study of a significant range of approaches of modern scientists to interpreting the concept of ‘control’ to find a clear and understandable definition not only of control but also of financial and state financial controls. The authors analysed the definition of financial control that revealed the advantages and disadvantages of the definitions provided by modern scientists. We concluded that the scientists mainly limit this concept to state control while subjects refer to state bodies. We also proposed a proper definition, taking into account the indicated shortcomings. Therefore, financial control is interpreted as an activity carried out by state and local self-government bodies, business entities, and citizens of Ukraine to ensure legality, financial discipline, and reasonableness in mobilising, distributing, and using funds and related material assets. At the same time, we aim to assess the economic efficiency of economic activity, avert and avoid obstacles that prevent the legal and rational use of property and funds, the expanded reproduction of production, satisfaction of state, collective, and private interests, and needs for economic management. In addition, we defined the purpose and tasks of financial control. In general, state financial control aims to prevent and detect financial offenses, bring the guilty to justice, ensure compensation for damages, and take measures to stop similar crimes from happening in the future. Its task is to ensure legality, efficiency, fiscal discipline, and optimality in the formation, distribution, possession, use, and disposal of assets as state property.